Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4067/s0717-95022019000100302
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Body Composition Differences in Female Police Officers

Abstract: Since performance in police occupations may depend on body composition and physical abilities, women are less likely to become police officers. However, information on age-related differences in body composition among female police officers (FPO) barely exists. Thus, this study aimed to investigate the association between age and body composition in FPO. Body composition of 95 FPO was assessed and divided into 4 age groups: 21-25 (age = 23.58 ± 0.84 years, body height [BH] = 1.61 ± 0.04 m, body mass [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…Hungary (Ihász et al), and the others from the region of Arabian Peninsula, i.e. from the UAE, Abu Dhabi to be precise (Kukic et al, 2019), showed that the average PBF value among Hungarian women was at the level of 34.32 %, and among those from UAE 40.09 %. When compared to Serbian women, respondents from Hungary had 16.9 % more body fat on average, whereas the UAE respondents had 28.9 % more, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Hungary (Ihász et al), and the others from the region of Arabian Peninsula, i.e. from the UAE, Abu Dhabi to be precise (Kukic et al, 2019), showed that the average PBF value among Hungarian women was at the level of 34.32 %, and among those from UAE 40.09 %. When compared to Serbian women, respondents from Hungary had 16.9 % more body fat on average, whereas the UAE respondents had 28.9 % more, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…It was previously found that different social, life and health factors, such as raising a family, maternity status, hormone status, professional-work environment and obligations, level of physical activity, diet habits etc. significantly influence variability factor of body composition changes among women (Thompson et al;Menotti et al;Gába & Pridalová;Sarayakin et al, 2018;Kukic et al, 2019). In a research conducted using the same measurement method and the same instrument, on a sample of women from Czech Republic, an average PBF value at the level of 29.1±8.9 % was measured.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations